The Political Economy of Bank Bailouts - Rainer Haselmann; Thomas Kick; Markus Behn; Vikrant Vig (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
In this paper, we examine how the institutional design affects the outcome of bank bailout decisions. In the German savings bank sector, distress events can be resolved by local politicians or a state-level association. We show that decisions by local politicians with close links to the bank are distorted by personal considerations: While distress events per se are not related to the electoral cycle, the probability of local politicians injecting taxpayers' money into a bank in distress is 30~percent lower in the year directly preceding an election. Using the electoral cycle as an instrument, we show that banks that are bailed out by local politicians experience less restructuring and perform considerably worse than banks that are supported by the savings bank association. Our findings illustrate that larger distance between banks and decision makers reduces distortions in the decision making process, which has implications for the design of bank regulation and supervision.
Keywords: G21; G28; D72; 330